Factor influencing the students toward studying in boarding school at MRSM Merbok, Kedah / Aiza Sofea Zon and Nur Syifa Nadia Zainol - Zon, Aiza Sofea; Nur Syifa Nadia, Zainol (2018)
Boarding schools viewed as conservative institutions that indoctrinate their students with conventional precepts, thereby reproducing the existing social order, while others have considered them "pro-gressive" institutions that socialize students to adopt new ideas and to assume leadership positions in society (Goffman 1961; Roden 1978; Weinberg 1967). Boarding school is a school in which there are various facilities provided for student accommodation and facilities near the location of the school (Bamford 1967). In boarding schools, students sleep, eat and do activities within the school environment. Furthermore, boarding school considered safe because the students do not live too far from school as they stay at the hostel provided (Bamford 1967).